Minimizing Color Difference in AAO-Based Coatings for Urban Camouflage - Yichen Wang; Xiujuan Reng; Dong Wang; Haifeng Liu; Yu Wu (Nanomaterials)
We explored anodic aluminum oxide (AAO) stealth materials combining low infrared emissivity and visible structural coloration through multi-parameter modulation. Using DC ion gold sputtering and UHV magnetron chromium sputtering, we successfully prepared an AAO stealth material with high-saturation visible structural coloration and low infrared emissivity (ε < 0.17). Quantitative evaluation based on the CIE Lab color difference model indicated that the gold-coated samples had high matching accuracy with PANTONE standard colors (<semantics>Δ<msubsup>Eab*</msubsup></semantics> < 1.6). The chromium-coated samples had slightly lower matching accuracy (<semantics>Δ<msubsup>Eab*</msubsup></semantics> < 3.0), but still displayed rich coloration, with color difference within human-perceptible tolerance limits.